Pancreatic panniculitis associated with pancreatic carcinoma: A case report. Issue 31 (August 2016) - Zhang, Guannan; Cao, Zhe; Yang, Gang; Wu, Wenming; Zhang, Taiping; Zhao, Yupei
Abstract: Introduction: Pancreatic panniculitis is a very rare complication of pancreatic cancer, most often accompanying rare acinar cell carcinoma. We herein report a case of pancreatic panniculitis that was associated with pancreatic mucinous adenocarcinoma. Patient information: A 57-year-old male was referred to our hospital for weight loss. A physical examination revealed subcutaneous nodules on his lower extremities. The blood test showed abnormal increases in amylase, lipase, and carbohydrate antigen 19–9 levels. A computed tomography scan detected a hypodense 2 × 1.5 cm solid mass with an unclear margin in the head of the pancreas. The biopsy of subcutaneous nodules on the lower extremities was conducted and revealed lobular panniculitis. Pancreatic cancer and pancreatic panniculitis were strongly suspected. After the administration of octreotide acetate and the Whipple procedure, the serous amylase and lipase levels returned to normal, and the pancreatic panniculitis had almost resolved by 4 weeks later. Conclusion: Pancreatic panniculitis is a rare complication of pancreatic cancer. However, in the presence of a pancreatic mass, as in this case, clinicians should be aware that panniculitis may be the sentinel of pancreatic carcinoma.